Exploring dancer experience and performance with visual sensor camera using NUI environment - Sidhu M.S.; Iqbal J. (Institute of Electrical and Electronics Engineers Inc., 2023)
User interfaces; Analysis; Analysis system; High-resolution depth; Interactive; Interactive feedback; Motion; Natural user interfaces; Visual realities; Feedback